Leaders’ Conversations: National Libraries in the Post-COVID-19 World - Soh, Lin Li; Laue, Michelle; Lim, Benita; Saleem, Mohamed (Access: An International Journal of Nepal Library Association, 2022)
The International Federation of Library Associations and Institutions (IFLA) Regional Office for Asia and Oceania and the National Library Board, Singapore jointly organized the inaugural Leaders’ Conversations in 2020. The first series of the Leaders’ Conversations focused on the future of the libraries in the Post-COVID-19 world and was held with the leaders of the various libraries. This report features enlightening insights from the library leaders from the national libraries, which are very much crucial for the operations of national libraries in today’s uncertain environment.